Infinite jest : caricature and satire from Leonardo to Levine ; [in conjunction with the Exhibition "Infinite Jest: Caricature and Satire From Leonardo to Levine" on view at The Metropolitan Museum of Art, New York, from September 13, 2011 through March 4, 2012] (Metropolitan Museum of Art, 2011)
"Shoot folly as it flies" : humor on paper / Constance C. McPhee with contributions by Nadine M. Orenstein -- Caricature and satire from Leonardo to Levine -- Elements of caricature -- Social satire -- Politics -- Celebrities